Remote assessment of heart rate and its fluctuations by smartphone camera - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2018)
Commercial smartphone cameras were evaluated regarding their potential to function as remote photoplethysmographic imaging (PPGI) systems in the visible light spectrum to record heart rate and its fluctuations. Camera recordings were assessed in various lighting and zooming conditions and validated against contact infrared photoplethysmography. Rhythmic and temporal characteristics of the recorded signals were analyzed by the wavelet transform, and compared by intraclass correlation coefficients. Only in the green wavelength band, remote recording of mean heart rate was found to be exact and valid, and fairly sufficient for the determination of the fluctuations of heart rate. The latest smartphone camera sensor technology has made great technological progress to function as a valid PPGI system. © 2018 IEEE.